PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS VII SMP NEGERI 5 KOTA PARIAMAN - Nurhidayati, Nurhidayati; Atmazaki, Atmazaki; Abdurahman, Abdurahman (Universitas Negeri Padang, 2016)
ABSTRACTÂ The purpose of this study was to describe the effect of the use of problem based learning models aided media beamed images to text short story writing skills of students of class VII SMP Negeri 5 Kota Pariaman. This research data is the result of the test scores of text short story writing skills using problem based learning models aided media beamed images. Data were collected through performance tests. The results of this study is there is influence-aided model of problem based learning media beamed images to text short story writing skills of students of class VII SMP Negeri 5 Kota Pariaman at significant level of 95% with degrees of freedom (n1 + n2) -2, which thitung>ttabel (7, 01> 1.68). H0and H1 accepted because the hypothesis testing results prove that thitung greater than ttabel.Â Kata kunci: Pengaruh, model PBL, gambar berseri, menulis, cerpenÂ